Formulation of natural drag-reducing agent from malabar spinach for aqueous liquid flowing in turbulent mode through pipelines - Ann, Lim Jo (2010)
In this study, the drag-reducing properties of mucilage extracted from the stem of the Malabar spinach in both aqueous liquids flowing in pipelines are investigated. Fluid flowing in turbulent through pipelines produce pressure drop as a result of friction resistance. Pumps are installed to reduce pressure drop; however this increases the costs of the pipeline system. Conventional drag-reducing agents include polymers, suspended solids and surfactants. Mucilage is a new member to this class of additives and has great potential as it is natural, cost-effective and biodegradable. An experimental piping rig was used to study the effects of Reynolds number, pipe length and mucilage concentration on drag reduction in water. The relationship between these factors and DR are discussed. The study shows that the maximum DR recorded was 78.2% at 300ppm concentration with internal pipe diameter of 0.0254m.